Study of Carbon, Phosphorus and Nitrogen in the Sediments of River Pamba - Koshy, Mathew (Asian Journal of Chemistry, 2010)
The sediment organic carbon (SOC), total phosphorus (TP) and total nitrogen (TN) of the sediment of the river Pamba, the third largest river flowing through central Kerala, has been studied, for a period of one year, by collecting samples from two stations. The samples were analysed. The results on analysis of SOC, TN and TP found that the concentrations were low and terrestrial in origin.